Can polar bears use terrestrial foods to offset lost ice‐based hunting opportunities?. Issue 3 (1st April 2015) - Rode, Karyn D; Robbins, Charles T; Nelson, Lynne; Amstrup, Steven C
Abstract : Increased land use by polar bears (Ursus maritimus ) due to climate‐change‐induced reduction of their sea‐ice habitat illustrates the impact of climate change on species distributions and the difficulty of conserving a large, highly specialized carnivore in the face of this global threat. Some authors have suggested that terrestrial food consumption by polar bears will help them withstand sea‐ice loss as they are forced to spend increasing amounts of time on land. Here, we evaluate the nutritional needs of polar bears as well as the physiological and environmental constraints that shape their use of terrestrial ecosystems. Only small numbers of polar bears have been documented consuming terrestrial foods even in modest quantities. Over much of the polar bear's range, limited terrestrial food availability supports only low densities of much smaller, resident brown bears (Ursus arctos ), which use low‐quality resources more efficiently and may compete with polar bears in these areas. Where consumption of terrestrial foods has been documented, polar bear body condition and survival rates have declined even as land use has increased. Thus far, observed consumption of terrestrial food by polar bears has been insufficient to offset lost ice‐based hunting opportunities but can have ecological consequences for other species. Warming‐induced loss of sea ice remains the primary threat faced by polar bears.